EFFECT OF MAGNETIC TREATMENT OF CUTTINGS AND IRRIGATION WATER ON VEGETATIVE PROPAGATION OF - Bashar Z. Kassab Bashy (Mesopotamia Journal of Agriculture)
Semi-hard wood cuttings of Carissa grandiflora planted at 15 April 2005 on river sand media, half of them were proposed to magnetic field 0.3 × 10-3 Tesla at the base of cutting for 30 second and other cuttings did not, each group divided into two halves, one irrigated by usual water ( non - magnetic water ) and the other irrigated with